Effect of Aloe vera as a local drug delivery agent in the management of periodontal diseases: A systematic review and meta-analysis - Ashwini Narendra Jadhav; Surekha Ramrao Rathod; Abhay Pandurang Kolte; Pranjali Vijaykumar Bawankar (Wolters Kluwer Medknow Publications, 2021)
Background: Aim of the present meta-analysis was to evaluate the effect of Aloe vera in various forms such as gel, mouthwash, and dentifrice on gingival and plaque index (PI) in comparison to various allopathic products such as chlorhexidine, metformin, chlorine dioxide, fluoridated toothpaste, and alendronate. Materials and Methods: A comprehensive electronic search was conducted on PubMed/MEDLINE, GOOGLE SCHOLAR, and HAND SEARCH of reference list of archived articles published till January 2020. Randomized controlled trials were searched comparing the Aloe vera product with other products which used PI and gingival index (GI) to evaluate the outcomes. Finally, nine studies assessing PI and four studies evaluating GI were considered for the meta-analysis. After extracting the information, a risk of bias was estimated. The standardized mean differences (SMDs) and fixed and random effect models were obtained from the mean treatment differences. Results: The estimates of SMD of PI from fixed effects (SMD = 0.271, 95% confidence interval [CI] = 0.00134-0.407, P < 0.001) and random effects (SMD = 0.288, 95% CI = 0.048-0.529, P = 0.019) were found slightly different, the models showed consistent results yielding positive and significant treatment effects. For GI fixed effects (SMD = 0.27, 95% CI = −0.035-0.575, P = 0.0803, not significant) and random effects (SMD = 0.259, 95% CI = 0.049-0.469, P = 0.016, significant) were found slightly different and positive. However, one model showed significant and another model showed nonsignificant treatment effects. Conclusion: Results from our meta-analyses confirmed the beneficial effects of A. vera in improving the periodontal parameters and hence may be considered as a safe alternative drug delivery agent for the management of periodontal diseases in future.